Evaluation of Yield Performance and Variation on its Adaptation-Related Traits of Hybrid Maize to Local Environment in Terengganu, Malaysia - Nozulaidi Nordin, Mohd; Khairi Che Lah, Mohd; Alias, Nadiawati; Musa Wan Muda, Wan; Mat, Nashriyah; Ngah, Norhayati (International Journal of Engineering and Technology, 2018)
The study evaluates the yield performance and adaptation-related traits of 16 hybrid maize to the local environment in Terengganu Malaysia. The seeds of 15 hybrid maize were supplied by CIMMYT (International Maize and Wheat Improvement Centre), Mexico and one commercial local hybrid maize (Sweet King) was used as a control. The soil type at the experimental area is BRIS Soil of Merchang series which represent most of the soil types in Terengganu Malaysia. Data recorded was time taken for the plant to produce male and female flower; plant and ear height; straw, ear, shell and grain dry weight; ear number; and ear length. Time taken to produce male and female flowers, plant and ear height, and ear length are significantly different among tested plants. Other plant traits and yield performance shows no significant different among tested plants. Overall, the local hybrid maize shows the best performance in term of time taken to produce male and female flowers and plant growth compared to other hybrid maize tested in this experiment. However, the traits and performance of hybrid maize A13 is comparable to the local hybrid. The correlation between plant traits are also varies. It can be concluded that hybrid maize A13 shows good performance at local environment and have a potential as commercial hybrid maize for cultivation in Terengganu, Malaysia.Â Â
Keywords: Hybrid maize; plant genotype; plant traits; yield performance.